A 'silent' skull metastatic follicular thyroid carcinoma mimicking as a benign scalp tumor in a pregnant woman. (12th January 2017) - Huang, Tsung-Chun; Cheng, Yu-Kai; Chen, Tsung-Wei; Hsu, Yung-Chang; Liu, En-Wei; Chen, Hsin-Han
Summary: Thyroid cancer with cranial metastasis in a pregnant woman is very rare. In the literature, most cases are diagnosed early from neurogenic signs or symptomatic thyroid gland. Pregnancy also contributes to a hesitation toward early surgical and medical treatments. We reported a scalp tumor in a physically healthy 37-year-old pregnant female with a follicular thyroid carcinoma (FTC) with lung, bone and cranial metastasis in initial presentation. Silent neurogenic and physical examinations make an early diagnosis very challenging. Resection of scalp and intracranial tumor, a thyroidectomy, post-operative radioactive iodine therapy and tyrosine kinase inhibitors were employed as treatment. The scalp tumor was confirmed as a metastatic follicular thyroid carcinoma via positive immunoreactivity for thyroglobulin and thyroid transcription factor 1 in tumor cells. Blood examination revealed an elevated thyroglobulin level (>5335 ng/mL). The patient was discharged without any neurological deficit. An asymptomatic scalp tumor in a pregnant woman with a normal thyroid disease history needs differential diagnosis from intracranial origin. Rapid progression and an elevated thyroglobulin level are the indicators that further image study is needed. Aggressive surgical excision of resectable thyroid gland and metastatic tumor are essential for a longer survival rate. There is nothing to indicate that a post-partum operation will worsen prognosis. Learning points: Follicular thyroid cancer with cranial metastasis in initial presentation can be asymptomatic. Follicular thyroid cancer with cranial metastasis in a pregnant woman can be treated after delivery. Rapid enlargement of scalp tumor is indicated for further image study even in a patient without any neurological deficit.